2016
DOI: 10.1007/s12017-016-8402-1
|View full text |Cite
|
Sign up to set email alerts
|

Does Concurrent Use of Some Botanicals Interfere with Treatment of Tuberculosis?

Abstract: Millions of individuals with active TB do not receive recommended treatments, and instead may use botanicals, or use botanicals concurrently with established treatments. Many botanicals protect against oxidative stress, but this can interfere with redox-dependent activation of isoniazid and other prodrugs used for prophylaxis and treatment of TB, as suggested by results of a recent clinical trial of the South African botanical Sutherlandia frutescens (L.) R. Br. (Sutherlandia). Here we provide a brief summary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Recently, our group demonstrated that an ethanol extract of S. frutescens down-regulated 50% of Hedgehog-responsive genes in murine prostate cancer cells (i.e., TRAMPC2) 6 . Also, we have previously reported that extracts from Sutherlandia can diminish NF-κB, ERK, AP-1, and JAK-STAT1 signaling in macrophages and microglia cells [8][9][10][11] .…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Recently, our group demonstrated that an ethanol extract of S. frutescens down-regulated 50% of Hedgehog-responsive genes in murine prostate cancer cells (i.e., TRAMPC2) 6 . Also, we have previously reported that extracts from Sutherlandia can diminish NF-κB, ERK, AP-1, and JAK-STAT1 signaling in macrophages and microglia cells [8][9][10][11] .…”
Section: Introductionmentioning
confidence: 91%
“…While there may be several health benefits associated with reduced production of TNF, there is evidence that Sutherlandia use could be problematic in some circumstances. TNF is known to play an important role in controlling tuberculosis 11,33 , which may explain why treatment with S. frutescens increased the risk of tuberculosis infection in a recent clinical trial 11,34 . Since, TNF production is increased during many other infectious diseases, such as: pertussis, African trypanosomiasis, amoebiasis, hepatitis B, and influenza A, it remains to be determined if Sutherlandia use in individuals with any of these infections might also be contraindicated.…”
mentioning
confidence: 99%
“…This requires health care practitioners to ensure a clear communication with patients regarding the possible negative impacts of simultaneous use of certain TMs and prescribed drugs. It was reported that the widely used Sutherlandia frutescens in the treatment of TB in countries of Southern African Development Community interfered with the isoniazid therapy, but the mechanism of this interaction was not clear [263,264]. Coadministration also resulted in the reduced bioavailability of ofloxacin [265], while piperine showed the ability to increase the bioavailability of the antituberculosis drug rifampicin [266][267][268].…”
Section: Need For Future Researchmentioning
confidence: 99%
“…When used concurrently with commonly prescribed medications, CAM may affect the function of P450s and transport proteins, changing the pharmacokinetic pro le of the prescribed medications (Folk et al, 2016). Patients utilize complementary and alternative medicine (CAM) before HIV diagnosis, and those who have been diagnosed with HIV continue to use it in conjunction with antiretroviral medication (ART) and/or Cotrimoxazole prophylaxis (Puoane et al, 2012).…”
Section: Introductionmentioning
confidence: 99%